Executive functions in understanding certain disabilities within an African context - Masuku, Mfundo Mandla; Sithole, Mbongeni Shadrack; Mthembu, Zinhle (Frontiers in Education, 2023)
Cognitive and social functioning are important aspects of the development of all children. In the transition from one stage of development to another, children are expected to master related skills. There is sufficient literature depicting that children with learning disabilities often experience challenges in a range of executive functions, which are necessary for the successful negotiation of their educational and life-related tasks. As a result, they may require appropriate intervention measures to enable them to address possible limitations. This paper examines the cognitive and social skills deficits that impact on the planning and decision-making outcomes of children with disabilities, using an Afrocentric approach. The Afrocentric paradigm is central in studying and understanding African experiences from an African perspective. Afrocentricity is used as an alternative knowledge system, which places the needs of Africans at the center of focus. In contrast to Eurocentric tendencies, the holistic being, in the African context, is understood and constituted as body, mind, and spirit. While there is sufficient Western literature acknowledging similar holistic views, and biopsychosocial and spiritual dimensions, this paper points out on the lack of emphasis on the latter dimension. The paper concludes that without providing relevant interventions on learner executive functions, the impairment of cognitive and social functioning is likely to continue.